Kontrak Perilaku dan Rutinitas Kelas untuk Siswa Sekolah Dasar: Studi Kasus di Lembaga Bahasa Inggris Non-Formal - Somariah Fitriani (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2018)
The objective of the study is to expound the importance of behavior contract and class routine activity as the first initiative step to reduce students’ misbehavior and improve their interaction among peers. The researcher conducted mini experiment of “behavior contract” and “class routine” in teaching primary students as a part of learning process in Intensive English Course (IEC) as one of non-formal English institutions. 16 students between 10 to 12 years old participated in the research. For data collection, this paper relies on participant observation, checklist, interviews and literature reviews. The researcher acted as a key instrument to observe, take note and check the lists of behavior contract agreed and signed between teacher and students with parents’ prior notice. The research has revealed that the students have shown better improvement in term of behavior and attitudes. They also exhibit better interaction and improve their English-speaking skill since all students study English. To infer, the role of teachers who become ultimate keys to quality learning and education in disseminating the idea of respect, character building for others has a profound effect on students’ behavior and attitudes so as to have mutual understanding.